Phosphorus slag-based environment-friendly self-cleaning bare concrete
The phosphorus slag-based environmentally friendly self-cleaning clean water concrete is solved by the phosphorus slag-based environmentally friendly self-cleaning clean water concrete, combined with superhydrophobic components and iron oxide pigment, and the existing clean water concrete is difficult to achieve hydrophobic self-cleaning, achieving efficient and environmentally friendly construction technology and good apparent quality.
Patent Information
- Application Number
- CN202411993382.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
After the existing clean water concrete reaches smooth and smooth water, it is difficult to achieve hydrophobic self-cleaning effect, and the coating effect is poor, the bonding effect is limited, the construction process is complex, and the cement occupies a high amount, which affects environmental protection and cost.
The phosphorus slag-based environmentally friendly self-cleaning clean water concrete is used, and molded by single-use stirring, combined with superhydrophobic components and iron oxide pigment to form a surface layer with hydrophobic effect, reducing the amount of cement, improving environmental protection and construction efficiency.
Self-cleaning clean water concrete formed with direct one-time stirring is achieved, which reduces the use of cement, improves the bonding interface of the hydrophobic layer, ensures the apparent quality and self-cleaning performance of the concrete, and reduces construction complexity and carbon emissions.
Smart Images

Figure BDA0005224088810000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of self-cleaning plain concrete, and in particular relates to phosphorus slag-based environmentally friendly self-cleaning plain concrete and a preparation method thereof. Background Art
[0002] In the current field of plain concrete, release agents and construction processes are mostly used to ensure that the surface of concrete is clear, smooth and flat. If you want to further achieve hydrophobic self-cleaning, you often need to wait until the concrete solidifies before spraying paint on the surface. In this way, not only are the effects of various types of paints obviously different, but the bonding effect between the paint and the concrete surface is limited. At the same time, spraying paint requires additional secondary treatment of the surface to ensure smoothness. The construction process is cumbersome and lengthy. At the same time, cement accounts for a high proportion of the cementitious material. For the current development of the concrete industry, it is urgent to improve the above problems. Summary of the invention
[0003] The present invention provides a phosphorus slag-based environmentally friendly self-cleaning plain concrete and a preparation method thereof, which realizes direct one-time stirring and molding to prepare self-cleaning plain concrete with a surface hydrophobic effect, and realizes the preparation of more environmentally friendly self-cleaning plain concrete with a large amount of mineral admixtures based on the phosphorus slag, and the maximum proportion of cement used is less than 25%.
[0004] The technical solution according to this application is:
[0005] A phosphorus slag-based environmentally friendly self-cleaning plain concrete, characterized in that the raw material components are in the following mass ratios: 140-240 parts of phosphorus slag: 50-80 parts of white cement: 120-160 parts of industrial solid waste composite powder: 11-17 parts of super-hydrophobic component: 690-780 parts of machine-made sand: 960-1020 parts of crushed stone: 155-165 parts of water: 6-11 parts of admixture.
[0006] Preferably, the mass ratio of the components in the super-hydrophobic component is: 9-15 parts of silane coupling agent: 3-8 parts of active silicon dioxide: 264-293 parts of deionized water: 11-17 parts of acrylate: 8-14 parts of polyvinyl alcohol: 1-3 parts of sodium hexadecylbenzene sulfonate: 3-5 parts of ammonium persulfate: 1-3 parts of iron oxide pigment.
[0007] Preferably, the silane coupling agent is one or more of vinyltriethoxysilane, acetyltrimethoxysilane, vinyltrimethoxysilane, and 3-acryloxypropyltrimethoxysilane.
[0008] Preferably, the active silicon dioxide has a specific surface area of 23 m 2 / g, purity 98%.
[0009] Preferably, the phosphorus slag is white powder with an activity of 92%.
[0010] Preferably, the white cement is white silicate 425 cement with a whiteness of more than 85%.
[0011] Preferably, the industrial solid waste composite powder is slag powder, steel slag powder, water slag powder,
[0012] Preferably, the machine-made sand is medium sand with a fineness modulus of 2.9 and a base powder content of less than 4%.
[0013] Preferably, the crushed stone is 0-10 mm crushed stone with a crushing value of 4.7;
[0014] Preferably, the iron oxide pigment is one or more of iron oxide red, iron oxide yellow, and iron oxide green;
[0015] Preferably, the super hydrophobic component preparation process is as follows:
[0016] Step 1: Weigh the raw materials in the super-hydrophobic component according to the mass ratio, put acrylate, polyvinyl alcohol and sodium hexadecylbenzene sulfonate into deionized water, use ammonium persulfate as an initiator, control the temperature at 75-90° C., and control the reaction time at 3-4 h to prepare a polyvinyl alcohol-acrylate polymer;
[0017] Step 2: The temperature is lowered to 30-40°C, and the silane coupling agent and active silica are added to the polyvinyl alcohol-acrylate polymer obtained in step 1, and stirred evenly and continuously at a speed of 30 r / min for 120-150 min. After being fully stirred, the mixture is cooled to room temperature and placed in a drying oven. After being air-dried at 20-22°C for 8-10 h, a super-repellent aqueous solution is obtained.
[0018] Step 3: Add the iron oxide pigment into the solution obtained in step 2, and stir well to obtain a super hydrophobic component.
[0019] The preparation principle of the super-hydrophobic component is as follows: using ammonium persulfate as an initiator, polyvinyl alcohol and acrylate in the solution undergo a condensation reaction to generate polyvinyl alcohol-acrylate polymer. During the process, sodium hexadecylbenzenesulfonate generates sulfonic acid groups with both hydrophilicity and hydrophobicity in the solution. After adding a silane coupling agent and active silica, the various substances in the solution are fully mixed after continuous stirring. The silane coupling agent couples with active silica and polyvinyl alcohol-acrylate polymer, and the composite solute of hexadecylbenzenesulfonic acid and silica-polyvinyl alcohol-acrylate polymer is evenly distributed in the solution. After air drying, part of the water is evaporated to increase the concentration and viscosity of the super-hydrophobic solution, and iron oxide pigment is added to fully dye the super-hydrophobic solution to obtain super-hydrophobic solutions of different colors.
[0020] Preferably, the preparation process of the phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete is as follows:
[0021] Step 1: Weigh white cement, phosphorus slag, industrial solid waste composite powder, super-hydrophobic component, machine-made sand, gravel, water, and admixture according to the mass ratio of each component;
[0022] Step 2: Add the white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand, and crushed stone weighed in step 1 according to the mass ratio of each component into a mixer and stir for 10 to 15 seconds to mix the powders and aggregates evenly;
[0023] Step 3: Add the water and admixture weighed in the mass ratio of each component in step 1 to the mixture stirred evenly in step 2, continue stirring in the mixer for 240-300 seconds, and after the concrete workability is formed, pour the superhydrophobic component into the concrete and stir for 30-60 seconds.
[0024] Step 4: Pour the concrete mixed evenly in step 3 into the mold, insert a vibrating rod into the concrete and continuously vibrate for 30 to 60 seconds, until a colored transparent film appears on the surface of the concrete, and then the phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is prepared.
[0025] The preparation principle of phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is as follows: after white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand and crushed stone are evenly mixed, water and admixtures are added and the mixture is halved for 240 to 300 seconds. At this time, the concrete is in a white freshly mixed concrete with good workability. The concrete is poured into a mold, and the super-hydrophobic component is added. After stirring for 30 to 60 seconds, the super-hydrophobic component is dispersed into the concrete. Due to the poor solubility of the super-hydrophobic component and the concrete, and the density of the concrete is much greater than that of the super-hydrophobic component, the super-hydrophobic component is squeezed around the concrete under the action of a vibrating rod, forming a super-hydrophobic component film around and on the surface of the concrete. After the concrete solidifies, the super-hydrophobic component is also bonded to the concrete surface. After demolding, phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is formed.
[0026] The beneficial effects of the present invention are:
[0027] (1) In the present invention, the amount of white cement in the concrete cementitious material is low, and the amount of phosphorus slag powder and industrial solid waste composite powder reaches more than 75%. The phosphorus slag powder has a certain retarding effect, reducing the early hydration heat. At the same time, the hydration reaction of the industrial solid waste composite powder and the phosphorus slag powder is after that of the white cement, and the generated hydration heat peak will be staggered with the hydration heat peak of the white cement, further reducing the early hydration heat, greatly reducing the possibility of early cracking of the concrete, and effectively ensuring the apparent quality of the concrete. At the same time, the cementitious system greatly reduces the amount of white cement, which can not only effectively reduce the carbon emissions of concrete production, but also further reduce the cost of concrete production;
[0028] (2) The main components of the hydrophobic component are hexadecylbenzene sulfonic acid groups and silica-polyvinyl alcohol-acrylate polymers. After vibration, the hydrophobic component forms a physical "encapsulation" on the concrete. In the early and middle stages of the concrete hydration reaction, active silica participates in the concrete hydration reaction, and the formed gel product tightly connects the concrete surface and the hydrophobic layer together. At this time, the hydrophobic ends of the polyvinyl alcohol-acrylate polymer uniformly point to the outside of the concrete. In addition, due to the continuous hydration reaction of the concrete, the excess water in the hydrophobic component first enters the interior of the concrete with the reaction. This part of water plays a certain curing role on the concrete. At the same time, as water continues to enter the concrete, the hydrophilic end of the dodecylbenzene sulfonic acid group faces the inside of the concrete, and the hydrophobic end faces the outside of the concrete. After the water is completely lost, a solid surface layer with super hydrophobic effect is formed on the surface of the concrete.
[0029] (3) Iron oxide pigments are added to the hydrophobic component instead of directly added to the concrete, which can effectively avoid the problems of reduced strength, reduced durability, and surface powdering caused by direct addition of pigments to the concrete. In addition, since iron oxide pigments do not react with the hydrophobic component, their color can be kept durable. After the phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete is completely demolded, not only does the concrete maintain its original strength, but the hydrophobic layer and concrete have a better bonding interface. In addition, due to the uniform orientation of the hydrophobic groups, the concrete hydrophobic layer has a stronger hydrophobic effect, reducing surface dust and water droplet aggregation, thereby playing a self-cleaning role. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below through specific implementation examples, which are intended to explain the present invention rather than to limit it.
[0031] Embodiment 1:
[0032] S1: Each component is weighed by mass: 9 parts of silane coupling agent, 3 parts of active silicon dioxide, 264 parts of deionized water, 11 parts of acrylate, 14 parts of polyvinyl alcohol, 1 part of sodium hexadecylbenzene sulfonate, 3 parts of ammonium persulfate, and 1 part of iron oxide pigment.
[0033] S2: Add the acrylate, polyvinyl alcohol and sodium hexadecylbenzene sulfonate weighed in S1 into deionized water, use ammonium persulfate as an initiator, control the temperature at 75°C, and control the reaction time at 4 hours to prepare a polyvinyl alcohol-acrylate polymer;
[0034] S3: The temperature is lowered to 30°C, and the silane coupling agent and active silica are added to the polyvinyl alcohol-acrylate polymer obtained in step 1, and stirred evenly and continuously at a speed of 30 r / min for 120 min. After fully stirring, the solution is cooled to room temperature and placed in a drying oven. After air-drying at 20°C for 8 h, a super-repellent aqueous solution is obtained.
[0035] S4: Adding the iron oxide pigment into the solution obtained in S3, stirring the mixture thoroughly to obtain a super hydrophobic component.
[0036] S5: Each component is weighed by mass, including 240 parts of phosphorus slag, 50 parts of white cement, 160 parts of industrial solid waste composite powder, 11 parts of superhydrophobic component, 690 parts of machine-made sand, 1020 parts of crushed stone, 155 parts of water, and 11 parts of admixture;
[0037] S6: Add the white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand and crushed stone weighed in S5 according to the mass ratio of each component into a mixer and stir for 10 seconds to mix the powders and aggregates evenly;
[0038] S7: Add the water and admixture weighed in S5 to the mixture stirred evenly in S4, and continue stirring in the mixer for 240 seconds. After the concrete workability is formed, pour the superhydrophobic component into the concrete and stir for 30 seconds.
[0039] S8: Pour the concrete mixed evenly in S7 into a mold, insert a vibrating rod into the concrete and continuously vibrate for 30 seconds until a colored transparent film appears on the surface of the concrete. At this time, phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is prepared.
[0040] Embodiment 2:
[0041] S1: Each component is weighed by mass: 15 parts of silane coupling agent, 8 parts of active silicon dioxide, 293 parts of deionized water, 17 parts of acrylate, 8 parts of polyvinyl alcohol, 3 parts of sodium hexadecylbenzene sulfonate, 5 parts of ammonium persulfate, and 3 parts of iron oxide pigment.
[0042] S2: Add the acrylate, polyvinyl alcohol and sodium hexadecylbenzene sulfonate weighed in S1 into deionized water, use ammonium persulfate as an initiator, control the temperature at 90°C, and control the reaction time at 3h to prepare a polyvinyl alcohol-acrylate polymer;
[0043] S3: The temperature is lowered to 40°C, and the silane coupling agent and active silica are added to the polyvinyl alcohol-acrylate polymer obtained in step 1, and stirred evenly and continuously at a speed of 30 r / min for 150 min. After being fully stirred, the mixture is cooled to room temperature and placed in a drying oven. After being air-dried at 20°C for 10 h, a super-repellent aqueous solution is obtained.
[0044] S4: Adding the iron oxide pigment into the solution obtained in S3, stirring the mixture thoroughly to obtain a super hydrophobic component.
[0045] S5: Each component is weighed by mass, including 140 parts of phosphorus slag, 80 parts of white cement, 120 parts of industrial solid waste composite powder, 17 parts of superhydrophobic component, 780 parts of machine-made sand, 960 parts of crushed stone, 165 parts of water, and 6 parts of admixture;
[0046] S6: Add the white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand and crushed stone weighed in S5 according to the mass ratio of each component into a mixer and stir for 15 seconds to mix the powders and aggregates evenly;
[0047] S7: Add the water and admixture weighed in S5 to the mixture stirred evenly in S4, continue stirring in the mixer for 300 seconds, and after the concrete workability is formed, pour the superhydrophobic component into the concrete and stir for 60 seconds.
[0048] S8: pour the concrete mixed evenly in S7 into a mold, insert a vibrating rod into the concrete and continuously vibrate for 60 seconds, thereby preparing phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete.
[0049] Embodiment 3:
[0050] S1: Each component is weighed by mass: 12 parts of silane coupling agent, 6 parts of active silicon dioxide, 276 parts of deionized water, 14 parts of acrylate, 12 parts of polyvinyl alcohol, 2 parts of sodium hexadecylbenzene sulfonate, 4 parts of ammonium persulfate, and 2 parts of iron oxide pigment.
[0051] S2: The acrylate, polyvinyl alcohol and sodium hexadecylbenzene sulfonate weighed in S1 are added into deionized water, ammonium persulfate is used as an initiator, the temperature is controlled at 82°C, and the reaction time is controlled at 2.5h to prepare a polyvinyl alcohol-acrylate polymer;
[0052] S3: The temperature is lowered to 35°C, and the silane coupling agent and active silica are added to the polyvinyl alcohol-acrylate polymer obtained in step 1, and stirred evenly and continuously at a speed of 30 r / min for 135 min. After being fully stirred, the solution is cooled to room temperature and placed in a drying oven. After being air-dried at 21°C for 9 h, a super-repellent aqueous solution is obtained.
[0053] S4: Adding the iron oxide pigment into the solution obtained in S3, stirring the mixture thoroughly to obtain a super hydrophobic component.
[0054] S5: Each component is weighed by mass, including 190 parts of phosphorus slag, 65 parts of white cement, 140 parts of industrial solid waste composite powder, 14 parts of superhydrophobic component, 780 parts of machine-made sand, 960 parts of crushed stone, 160 parts of water, and 8 parts of admixture;
[0055] S6: Add the white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand and crushed stone weighed in S5 according to the mass ratio of each component into a mixer and stir for 12 seconds to mix the powders and aggregates evenly;
[0056] S7: Add the water and admixture weighed in S5 to the mixture stirred evenly in S4, and continue stirring in the mixer for 270 seconds. After the concrete workability is formed, pour the superhydrophobic component into the concrete and stir for 45 seconds.
[0057] S8: Pour the concrete mixed evenly in S7 into a mold, insert a vibrating rod into the concrete and continuously vibrate for 45 seconds, thereby preparing phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete.
[0058] Comparative Example 1:
[0059] The difference between this comparative example and Example 3 is that in step S7, no super-hydrophobic component is added;
[0060] Comparative Example 2:
[0061] The difference between this comparative example and Example 3 is that in step S4, the iron oxide pigment is not put into the hydrophobic solution in step S3; in step S6, the iron oxide pigment and the components are weighed and stirred together;
[0062] Comparative Example 3:
[0063] The difference between this comparative example and Example 3 is that in step S7, the super-hydrophobic component is not poured into the concrete; in step S8, the super-hydrophobic component is sprayed on the hardened surface of the concrete after the concrete is hardened and demoulded;
[0064] Comparative Example 4:
[0065] The difference between this comparative example and Example 3 is that in step S7, the super hydrophobic component in this patent is not added, and the silicone hydrophobic agent is poured in.
[0066] Performance test: The compressive strength, peel strength, surface quality and self-cleaning performance of the phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete prepared in Examples 1-3 and Comparative Examples 1-4 were tested after curing for 28 days. The self-cleaning performance test method is to evenly apply dust below 0.75um on the surface of the test block, and use a spray device to simulate the ratio of the smooth area to the dust residual area after rain scouring. The performance test results are as follows:
[0067] Table 1 Concrete performance test results
[0068]
[0069] Data analysis:As can be seen from Example 1-Example 3, the phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete prepared by the present invention covers multiple different strength grades of concrete, and when each raw material is changed within the design range, phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete always maintains good self-cleaning performance and apparent quality, and all have higher peel strength, and peel strength rises as concrete strength grade rises. It can also be learned from Comparative Example 1-Comparative Example 4 that the super hydrophobic agent prepared using the present invention, without affecting compressive strength, its peel strength, self-cleaning performance and apparent quality are greatly improved. And the present invention is with phosphorus slag and industrial solid waste composite powder as raw materials, by recycling it after realizing the circulation of bulk industrial solid waste in application, reducing the addition of cement, reducing the carbon emission in concrete production process, meeting green, low-carbon environmental protection requirements.
[0070] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A phosphorus slag-based environmentally friendly self-cleaning plain concrete, characterized in that: The mass ratio of each raw material component is: 140-240 parts of phosphorus slag: 50-80 parts of white cement: 120-160 parts of industrial solid waste composite powder: 11-17 parts of super hydrophobic component: 690-780 parts of machine-made sand: 960-1020 parts of crushed stone: 155-165 parts of water: 6-11 parts of admixture.
2. According to claim 1, it is characterized in that: The weight ratio of the components in the super hydrophobic component is: 9-15 parts of silane coupling agent: 3-8 parts of active silicon dioxide: 264-293 parts of deionized water: 11-17 parts of acrylate: 8-14 parts of polyvinyl alcohol: 1-3 parts of sodium hexadecylbenzene sulfonate: 3-5 parts of ammonium persulfate: 1-3 parts of iron oxide pigment.
3. The super-hydrophobic component according to claim 2, characterized in that: The silane coupling agent is one or more of vinyl triethoxysilane, acetyl trimethoxysilane, vinyl trimethoxysilane, and 3-propyleneoxypropyl trimethoxysilane.
4. The super-hydrophobic component according to claim 2, characterized in that: The specific surface area of the active silica is 23m 2 / g, purity 98%.
5. The phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete according to claim 1, characterized in that: The white cement is white silicate 425 cement with a whiteness of more than 85%.
6. The phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete according to claim 1, characterized in that: The industrial solid waste composite powder is slag powder, steel slag powder and water slag powder.
7. The phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete according to claim 1, characterized in that: The machine-made sand is medium sand with a fineness modulus of 2.9 and a bottom powder content of less than 4%. The crushed stone is 0-10 mm crushed stone with a crushing value of 4.
7.
8. The phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete according to claim 1, characterized in that: The super hydrophobic component preparation process is as follows: Step 1: Weigh the raw materials in the super-hydrophobic component according to the mass ratio, put acrylate, polyvinyl alcohol and sodium hexadecylbenzene sulfonate into deionized water, use ammonium persulfate as an initiator, control the temperature at 75-90° C., and control the reaction time at 3-4 h to prepare a polyvinyl alcohol-acrylate polymer; Step 2: The temperature is lowered to 30-40° C., and the silane coupling agent and active silica are added to the polyvinyl alcohol-acrylate polymer obtained in step 1. The mixture is stirred evenly and continuously at a speed of 30 r / min for 120-150 min. The mixture is stirred evenly and then cooled to room temperature for storage. Step 3: Add the iron oxide pigment into the solution obtained in step 2, and stir well to obtain a super hydrophobic component.
9. The phosphorus slag-based environmentally friendly hydrophobic self-cleaning plain concrete according to claim 1, characterized in that: The preparation process of the phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is as follows: Step 1: Weigh white cement, phosphorus slag, super-hydrophobic component, machine-made sand, gravel, water and admixture according to the mass ratio of each component; Step 2: Add the white cement, phosphorus slag, industrial solid waste composite powder, machine-made sand, and crushed stone weighed in step 1 according to the mass ratio of each component into a mixer and stir for 10 to 15 seconds to mix the powders and aggregates evenly; Step 3: Add the water and admixture weighed in the mass ratio of each component in step 1 to the mixture stirred evenly in step 2, continue stirring in the mixer for 240-300 seconds, and after the concrete workability is formed, pour the superhydrophobic component into the concrete and stir for 30-60 seconds. Step 4: Pour the concrete mixed evenly in step 3 into the mold, insert a vibrating rod into the concrete and continuously vibrate for 30 to 60 seconds, until a colored transparent film appears on the surface of the concrete, and then the phosphorus slag-based environmentally friendly hydrophobic self-cleaning clear water concrete is prepared.
Citation Information
Patent Citations
Super-hydrophobic coating for corrosion resistance and freeze thawing resistance of concrete and preparation method thereof
CN111205767A
Super-hydrophobic concrete based on machine-made sand with high stone powder content and preparation method thereof
CN114085052A
Concrete mortar and construction method
CN114180893A
Super-hydrophobic self-cleaning coating for cement-based surface, coating and preparation method of super-hydrophobic self-cleaning coating
CN114956684A
Mirror-surface bare concrete doped with bare water powder and construction process of mirror-surface bare concrete
CN115974483A